A Transitory Settlement on the Way back to Venezuela: A Tale of Vulnerability, Exception, and Migrant Resistance in times of Covid-19 - Palma-Gutierrez, Mauricio (2021)
Due to the economic and social consequences of the Covid-19 emergency of 2020, many vulnerable Venezuelan migrants scattered across South America decided to return to their country overland. Simultaneously, exceptional measures imposed during the pandemic resulted in increased domestic and international political constraints to their mobility. Different strategies to resist and overcome such restrictions emerged in this scenario. Drawing upon the concept of Temporary Migrant Multiplicities (Tazzioli, 2020), I analyse how to camp became one of those collective strategies. I present the results of a digital ethnography focusing on a transitory settlement built (and later abandoned) by some 500 persons returning to Venezuela, between May and July 2020 in the outskirts of Bogotá (Colombia). I thereby explore how vulnerabilities can turn into vehicles of resistance in contexts of arbitrary control over precarised human mobility, such as Covid-19 exceptional politics.